Thailand : Selected Issues. (IMF Staff Country Reports; Country Report, 2008)
To estimate the New Keynesian model, we use four key macroeconomic series for Thailand. The priors are chosen to reflect general considerations of the appropriate model dynamics and our judgment about the Thai economy. The model is solved initially so that the baseline forecast replicates staff baseline projections over the medium term. We analyze two main risk scenarios, and estimate that the output in Thailand may decline by up to 0.9 percent relative to the baseline. However, the adverse impact on Thai output is likely to be smaller than suggested above.